2021
DOI: 10.1111/joca.12417
|View full text |Cite
|
Sign up to set email alerts
|

Measurement error in research on financial literacy: How much error is there and how does it influence effect size estimates?

Abstract: Financial literacy is often measured with only three to five questions, suggesting challenges with achieving respectable levels of internal consistency reliability. Based on our review, we found financial literacy tests composed of three and five test questions yielded mean reliability estimates of 0.40 (k = 7; N = 167,075) and 0.54 (k = 8; N = 57,937), respectively: values less than minimally acceptable for even exploratory research. Based on our more comprehensive review of 52 samples and a variety of financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Fernandes et al ( 2014)'s measure was created and validated via vigorous psychometric test-ing and achieves one of the highest internal consistency reliability scores of any financial literacy measure (Gignac and Ooi, 2022) and with that, it is one of the most important financial literacy measures both for academic research and for policy making. Nevertheless, we have shown how the questionnaire cannot continue to be used in its current format, as on-going changes in legislation invalidate one of its questions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fernandes et al ( 2014)'s measure was created and validated via vigorous psychometric test-ing and achieves one of the highest internal consistency reliability scores of any financial literacy measure (Gignac and Ooi, 2022) and with that, it is one of the most important financial literacy measures both for academic research and for policy making. Nevertheless, we have shown how the questionnaire cannot continue to be used in its current format, as on-going changes in legislation invalidate one of its questions.…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive review of different financial literacy measures, evaluating 71 individual studies, Huston (2010) suggested that the use of questionnaires with 12 to 20 items, measuring wider concepts with higher psychometric validity, is a better approach to the measurement of financial literacy. Similarly, Gignac and Ooi (2022) concluded that commonly used short questionnaires with only three or five questions have internal reliability values below what is minimally accepted and recommended a minimum of 13 to 15 questions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, given that our financial knowledge scores were measured with a small number of measurement items (four to five), they may have suffered from low reliability. As discussed in Gignac and Ooi (2022), a low reliability in the scale could lead to underestimated coefficient estimates in regression analyses. Future research should assess how much reliability can be recovered with additional measurement items and which topics should be included to maintain a satisfactory degree of validity.…”
Section: Discussionmentioning
confidence: 99%
“… Limitations have been raised in terms of content coverage (Schmeiser & Seligman, 2013), focusing on knowledge rather than skills (Fernandes et al, 2014), and measurement error due to number of items (Gignac & Ooi, 2022). …”
mentioning
confidence: 99%